2022
DOI: 10.52711/2231-5691.2022.00048
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Warning letters Issued by US FDA Over 2019-2021

Abstract: The United States Food and Drug Administration (US FDA) is a department of health and human services federal agency. If the FDA notices major violations of federal regulations, it sends warning letters to pharmaceutical makers, distributors, and clinical investigators. The nature of the infractions discovered, as well as the FDA's proposed corrective activities, are detailed in these warning letters. Following the completion of the corrective activities, the recipient may request a follow-up inspection. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Only few dental studies have evaluated the quality of EDR data. 5 6 8 12 20 21 22 23 For example, Patel et al compared the self-reported cardiovascular disease (CVD) information with dental patients' medical records. They found low to no agreement and concluded that self-reported CVD information in the EDR may not be reliable research sources compared with electronic medical records.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only few dental studies have evaluated the quality of EDR data. 5 6 8 12 20 21 22 23 For example, Patel et al compared the self-reported cardiovascular disease (CVD) information with dental patients' medical records. They found low to no agreement and concluded that self-reported CVD information in the EDR may not be reliable research sources compared with electronic medical records.…”
Section: Discussionmentioning
confidence: 99%
“…EDR data also provide longitudinal patient care information for periodontal disease (PD) research. 12 13 PD is one of the most prevalent dental diseases which may cause tooth loss and poor quality of life if left untreated. 14 15 The prevalence of PD is high worldwide.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly known as the 'spade flower' or 'pink ladies slipper' [26]. It grows mainly in the warmer parts of India [27] and is also found distributed in the subtropical and tropical regions of the world [28] Traditionally this herb is used to treat both simple and complicated diseases and disorders [29] such as urinary infections, diarrhea and leucorrhoea. The phytochemical screening of Hybanthus enneaspermus has interpreted the presence of different bioactive compounds, namely alkaloids, flavonoids, phenols, tannins, sterols, nitro compounds and amines [30,31].…”
Section: Introductionmentioning
confidence: 99%